Comprehensive Approach to Cancer Pain in Pediatric Patients - Alexis Ramón Pineda González; Grettel Águila Calero; Anaelys Acosta Hernández; Marilyn Ramírez Méndez (Revista Finlay)
Cancer was considered a rare disease in children and adolescents; however, in recent years there has indicate that each year more than 160 thousand children are diagnosed. Pain is a cardinal symptom been a considerable increase in this disease. According to the International Union Against Cancer, statistics in these patients. The evaluation is complex and requires training in the use of scales designed and validated for different ages. Managing cancer pain in children is a great challenge, but at the same times an opportunity for health personnel to exercise their knowledge and skills to help them. This work aims to expose the main characteristics of pain from cancer in pediatrics, its evaluation and management, based on the pathophysiological knowledge, taking into account the aspects referenced in the most current specialized literature. All through a comprehensive approach that includes both pharmacological and non-pharmacological measures.